PENGARUH KUALITAS KEHIDUPAN KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN DI PT. AGUNG AUTOMALL CABANG SOEKARNO HATTA PEKANBARU - Mardiki Prajuanturi; Susi Hendriani; Kurniawaty Fitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research was conducted at PT. Agung Automall Branch Soekarno Hatta Pekanbaru with the aim to know the influence of variables Influence Quality of Work Life And Organizational Commitment To Employee Performance in PT. Agung Automall Branch Soekarno Hatta Pekanbaru. This study uses primary data that is data obtained from interviews and giving questionnaires to all employees of PT. Agung Automall Branch Soekarno Hatta Pekanbaru. Secondary data obtained related to the object and organizational structure of the population in this study were all employees who amounted to 75 people and sampled. The method of analysis used in this study is multiple linear regression method. From the results of tests that have been done, simultaneous regression test (Test-F) shows that the variable Quality of Work Life And Organizational Commitment simultaneously have a significant effect on Employee Performance. From the results of partial tests (Test-t) indicates that the variable Quality of Work Life and Organizational Commitment have a significant effect on Employee Performance. The result of calculation of coefficient of determination (R2) is equal to 0,646 or equal to 64,6% which mean, variable of Quality of Work Life And Commitment of Organization together influence to Employee Performance, while the rest 35,4% influenced by other variables not examined in this research.Keywords : Quality of life, Commitment and Employees performance